Cleoserrata (Cleomaceae): taxonomic considerations and a new species - Neto, Raimundo Luciano Soares; Barbosa, Maria Regina De Vasconcellos; Roalson, Eric H. (Phytotaxa, 2017)
Cleoserrata is a small genus of Cleomaceae that currently includes only two species. We describe here a new species of the genus that is endemic to eastern Brazil, propose two new combinations, review the nomenclature of the species already circumscribed, propose the lectotypification and synonymization associated with those species, and present commentaries concerning their morphological aspects, geographic distributions, relationships of affinity, illustrations, as well as a key for the identification of the species.